Géographie et politiques de l’aide d’urgence au Bangladesh ; les désastres engendrés par le typhon Sidr, le 16 novembre 2007 - Marianne Viot; Mouhssine Ennaïmi (EchoGéo)
Sidr typhoon struck the Southern districts in Bangladesh on November 16, 2007 (4000 victims, 8 millions of displaced people / homeless). The discussed reputation of this country supports the attention of the international opinion to him. Thanks to its experience about natural hazards and to a broad humanitarian organizations network, the prevention of the catastrophe and the management of emergency aid made it possible to limit the human lives losses. A good relief aid management offered the opportunity of quickly switching from an emergency to a development stage.Still, the situation remains complex and the country has not overcome the economic and social depression which characterizes it.